2021
DOI: 10.3390/land10010037
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Influence of Microclimate on Pedestrian Volume According to Land-Use

Abstract: Identifying how the urban environment affects pedestrian volume is a traditional urban planning topic. Recently, because of climate change and air pollution, interest in the effects of urban microclimates has been increasing. However, it is unclear whether the effects of microclimate on pedestrian volume can vary depending on the urban environment. This study determines whether microclimate’s influence on pedestrian volume differs according to land-use in the urban environment in Seoul, Korea. We constructed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Street furniture, sidewalk configuration, and other streetscape features are also found to have a significant relationship with PV [35,37,39]. Moreover, other studies considered the thermal comfort and microclimate factors [39,41,42]. Rodríguez et al used the rainfall among the weather elements as a control variable and found a significant negative correlation between rainfall and PV [39].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Street furniture, sidewalk configuration, and other streetscape features are also found to have a significant relationship with PV [35,37,39]. Moreover, other studies considered the thermal comfort and microclimate factors [39,41,42]. Rodríguez et al used the rainfall among the weather elements as a control variable and found a significant negative correlation between rainfall and PV [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rodríguez et al used the rainfall among the weather elements as a control variable and found a significant negative correlation between rainfall and PV [39]. Chung et al and Kim's team found that PM10 concentration and precipitation significantly negatively affected PV [41,42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the problem of the urban thermal environment, the increase in traffic and energy use in dense cities has led to an increase in fine dust emissions, resulting in atmospheric environmental problems [6]. Fine dust is a harmful substance that causes lung and heart diseases when exposed for a long time, possibly leading to death [7,8]. In 2019, the annual average concentration of PM 2.5 in South Korea was 24.8 µg/m 3 , the worst among OECD countries [9].…”
Section: Introductionmentioning
confidence: 99%